Changes in Hydrological Response of Forest Conversion to Agroforestry and Rainfed Agriculture in Renggung Watershed, Lombok, Eastern Indonesia - Muhamad Husni Idris; Mahrup Mahrup (Jurnal Manajemen Hutan Tropika, 2017)
Forest is an ideal ecosystem for a hydrological cycle, however converting forests to agroforestry or rainfed agriculture is inevitable.  This study elaborates a hydrological response of infiltration, runoff, and soil moisture in three land uses at Renggung watershed.  Field measurements were conducted in 2014−2015 in those system with soil types of entisols at upstream, inceptisols at the middle, and vertisols at downstream.  Results showed that constant infiltration rate at upstream in forest was 55.6 cm hr-1, in 15−30 years agroforestry was 32.4 cm hr-1 on average and in rainfed was 26.4 cm hr-1.  Infiltration in agroforestry at the middle and downstream was 16.8 cm hr-1 and 11.2 cm hr-1, respectively, while in rainfed was 2.4 cm hr-1 and 4.8 cm hr-1.  Runoff at upstream with 29.3 mm hr-1 rainfall in forest was zero, in agroforestry was 0.026 mm hr-1 and in rainfed was 0.071 mm hr-1.  Runoff in agroforestry at the middle and downstream with 37.1 mm hr-1 and 23.8 mm hr-1 rainfall were 0.045 mm hr-1, and 0.026 mm hr-1.  There was a half and one third of that in rainfed.  Soil water content in successive order from high to low was in forest, agroforestry, and rainfed.  So, capacity of agroforestry in sustaining the hydrology cycle was in between forests and rainfed agriculture.